Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPAS Melalui Model Kooperatif Tipe Jigsaw Dikelas V SD Inpres 2 Tatura: Improving Student Learning Outcomes in the IPAS Subject Using the Jigsaw Cooperative Learning Model in Grade V at SD Inpres 2 Tatura - Nursyatipa Nursyatipa; Nashrullah Nashrullah; Muslim AR; Herlina Herlina; Rangga Putera Boroallo (ITScience (Information Technology and Science), 2026)
This study was motivated by the low student learning outcomes in the Natural and Social Sciences (IPAS) subject among fifth-grade students at SD Inpres 2 Tatura. A teacher-centered instructional approach resulted in students being less active, unfocused, and disengaged from learning activities. The study aimed to improve student learning outcomes by implementing the Jigsaw cooperative learning model in science instruction. A Classroom Action Research (CAR) design was employed, utilizing the Kemmis and McTaggart model, which comprises the stages of planning, action implementation, observation, and reflection. The study was conducted over two cycles with 26 fifth-grade students at SD Inpres 2 Tatura. Data collection techniques included tests, observations, interviews, and documentation. The results indicate that implementing the Jigsaw cooperative learning model successfully improved student learning outcomes. At the pre-action stage, the class mastery rate was only 34.61%, rising to 65.38% in the first cycle. Furthermore, teacher and student engagement during the learning process improved, reaching a